The Institutional Mechanism of Ensuring for Meeting Commitments under International Treaties: Definition and Basic Elements (Summary) - N. S. Simonova (Nikitenko) (Московский журнал международного права, 2013)
In the international relations practice as well as in the international law doctrine there is no unified approach to define and comprehend the essence of the mechanism of ensuring for meeting commitments under international treaties. An article deals with the definition of such mechanism as a system of international law institutes, the regulations of which, being applied, really ensure for meeting commitments under international treaties. At the same the main conditions of obligation and conscientiousness unite all the institutes. The basic elements of the institutional mechanism of ensuring for meeting commitments under international treaties are: institutes of obligation and conscientiousness, international and internal means to ensure for meeting commitments under international treaties, institutes of courts and international organizations, institute of responsibility and liability. Moreover, characteristics of the basic elements of the institutional mechanism of ensuring for meeting commitments under international treaties are contained in the article.